Connected creativity – a human centered community innovation platform in the context of product generation engineering. (22nd February 2018) - Albers, Albert; Maul, Ludwig; Heismann, Robert; Bursac, Nikola
Abstract : In this paper, a concept for a community innovation platform is introduced focusing on human behavior of motivation and barriers in the context of product generation development. Building on the state of the art, a three year case study in cooperation with Dr. Ing. h.c. F. Porsche AG is at the core. In the first step of the study, a questionnaire and interviews are used to point out that a new attractive channel for ideas is needed. The three perspectives of users, experts and stakeholders are investigated in order to discover needs and preferences. Based on these findings, in a second step, a software prototype was designed and introduced in a pilot project with more than 200 users. Using a questionnaire and expert workshops, in the final step, this project is evaluated as appealing to the community, and the generated content is demonstrated to be valuable to specific activities of product generation development.